2021
DOI: 10.1177/20563051211019004
|View full text |Cite
|
Sign up to set email alerts
|

Studying Reddit: A Systematic Overview of Disciplines, Approaches, Methods, and Ethics

Abstract: This article offers a systematic analysis of 727 manuscripts that used Reddit as a data source, published between 2010 and 2020. Our analysis reveals the increasing growth in use of Reddit as a data source, the range of disciplines this research is occurring in, how researchers are getting access to Reddit data, the characteristics of the datasets researchers are using, the subreddits and topics being studied, the kinds of analysis and methods researchers are engaging in, and the emerging ethical questions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
183
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(191 citation statements)
references
References 45 publications
7
183
0
1
Order By: Relevance
“…The CI subreddit, ‘r/Cochlearimplants’, currently has over 2400 members. 17 Although Reddit is increasingly recognised as a valuable source of data in many other medical specialties, 18 r/Cochlearimplants has not been examined thus far. An exploration of this subreddit, to identify common questions posed by prospective CI users, would allow clinicians to provide more detailed information to those wishing to consider implantation.…”
Section: Introductionmentioning
confidence: 99%
“…The CI subreddit, ‘r/Cochlearimplants’, currently has over 2400 members. 17 Although Reddit is increasingly recognised as a valuable source of data in many other medical specialties, 18 r/Cochlearimplants has not been examined thus far. An exploration of this subreddit, to identify common questions posed by prospective CI users, would allow clinicians to provide more detailed information to those wishing to consider implantation.…”
Section: Introductionmentioning
confidence: 99%
“…Underscoring Reddit's importance in academic research, a recent review found more than 700 studies leveraging data sets from Reddit over the 2010–2020 period (i.e. Proferes et al, 2021 ). The website is a collection of independently moderated subcommunities—known as subreddits—organized around shared interests by subscribers.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is based on Reddit data; thus, it is useful to point out some attendant limitations of Reddit that have a bearing on the interpretation of our findings. The Reddit user base is mostly young (58% in the 18–34 years range), male (57%), and resides in the USA (plurality of 49%) ( Proferes et al, 2021 ; Statista, 2021 ). Our findings should be understood incorporating that context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A sizable portion of social science research involving big data has used datasets obtained from publicly accessible platforms such as social media websites, including Twitter and Reddit (Golder and Macy, 2014; Proferes et al, 2021). Although there is a common practice toward anonymizing and deidentifying individual records when analyzing big data, major ethical issues remain unsettled for these sources on key topics regarding consent, privacy, and the definition of “human subjects”-based research.…”
Section: Introductionmentioning
confidence: 99%